OPTIMALISASI PEMANFAATAN BIJIH NIKEL KADAR RENDAH DENGAN METODE BLENDING DI PT. ANTAM Tbk. UBPN SULTRA - -, Musnajam (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
Nickel ore is in the region Pomalaa, including the type formed by lateritic weathering of ultramafic rocks (peridotite, serpentine) mineral-rich olivine ((Mg, Fe) 2SiO4) and piroksin (AB Si2O6), The study was conducted to determine the handling and utilization of low grade nickel ore is carried out by PT Antam Tbk. UBPN Southeast Sulawesi. From the research, found that the amount of tonnage of low grade nickel ore (COG <1.8% Ni) compared with high-grade nickel ore (COG> 1.8% Ni). It requires handling as well as on the optimal utilization of low grade nickel ore, which in turn will support the survival of the company.